The Implementation of the GASING Method Integrated with the Megowak-Gowakan Game: A One-Group Pretest-Posttest Study on Mathematics Anxiety of Elementary Students - I Gede Fajar Dian Mahendra; Dinie Anggraeni Dewi (FKIP - Universitas Riau, 2026)
Mathematics anxiety is widely recognized as a psychological factor that can hinder elementary students’ engagement and academic performance in mathematics. This study examined changes in students’ mathematics anxiety following the implementation of the GASING (Easy, Fun, and Enjoyable) method integrated with the Balinese traditional game Megowak-gowakan. A quantitative quasi-experimental approach was applied using a one-group pretest-posttest design. The study did not include a control group, and the analysis was based on internal comparisons of pretest and posttest scores. The participants were 64 elementary school students from four districts in Bangli Regency, Bali. Data were collected through a validated mathematics anxiety questionnaire and analyzed using the N-Gain formula with SPSS version 30. The findings revealed a decrease in the mean anxiety score from 74.5 (pretest) to 52.3 (posttest), with an overall N-Gain of 0.58, indicating a moderate level of improvement. While the results demonstrate meaningful reductions in anxiety levels following the intervention, the absence of a comparison group limits the extent to which causal inferences can be drawn. Further studies employing controlled experimental designs are recommended to provide stronger empirical confirmation.